Fundamentos clínicos del consejo genético en cáncer hereditario - López, Ana; Lastra, Enrique; Nieto, Beatriz; García, María; Bayona, Cristina; Fonseca, Eva; Hernando, Blanca; Hernández, Rosario; García-girón, Carlos (Psicooncología, 2005)
We describe the Genetic Counseling as the translation of the hereditary cancer knowledge to the clinical practice. Genetic counseling is a process for information, which takes place at the Genetic Counseling Units, where individual cancer risk and mutation risk are estimated, genetic tests are performed authorized through the Informed Consent Document, the genetic test?s results are discussed, and screening and risk reducing strategies are recommended. The genetic test is offered when there is a suitable gene for the study, with meaningful results for the diagnosis of the hereditay syndrome and for the medical and surgical management of individuals at risk. It is essential that the genetic test be done within the Genetic Counseling before and after the test.